HUBUNGAN USIA MENARCHE DENGAN TERJADINYA MENOPAUSE DI WILAYAH KERJA PUSKESMAS KUSUMA BANGSA KOTA PEKALONGAN TAHUN 2016 - Ta’adi Ta' adi; Hartati Hartati; Millatin Puspaningtyas (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2016)
ALONG WITH THE INCREASE OF AGE, AT A TIME OF GROWTH AND DEVELOPMENT WILL BE STALLED. SUCH CHANGES USUALLY OCCUR IN THE AGING PROCESS, BECAUSE IN THIS PROCESS MANY PHYSICAL AND PSYCHOLOGICAL CHANGES. THE CHANGES ARE MOST COMMON IN WOMEN BECAUSE OF THE AGING PROCESS PHASES WHICH OCCURRED A MENOPAUSE. MENOPAUSE IS A NATURAL THING TO EVERY WOMAN, BUT IT IS STILL A SCARY THING FOR SOME WOMEN BECAUSE HE WAS ALREADY OLD AND NO LONGER USEFUL. THE PURPOSE OF THIS STUDY WAS TO DETERMINE THE RELATIONSHIP OF AGE OF MENARCHE TO MENOPAUSE IN PUSKESMAS KUSUMA BANGSA PEKALONGAN. THE STUDY DESIGN WAS DESCRIPTIVE ANALYTIC DESIGN WITH CROSS SECTIONAL APPROACH. THE POPULATION OF THIS RESEARCH IS THE MOTHER PRALANSIA MANY AS 3316 PEOPLE, WHILE THE SAMPLE USING PROPORTIONAL RANDOM SAMPLING AS MUCH AS 98 SAMPLES. DATA COLLECTION TOOLS BY USING A QUESTIONNAIRE. DATA WERE ANALYZED USING PEARSON PRODUCT MOMENT. THE RESULT SHOWED THAT MOST CATEGORIES OF MOTHERS MENOPAUSE AT THE AGE OF 53 YEARS. PEARSON PRODUCT MOMENT OF THE TEST BETWEEN THE AGE OF MENARCHE TO MENOPAUSE OBTAINED SIGNIFICANT CORRELATION BETWEEN THE AGE OF MENARCHE TO MENOPAUSE AGE (P VALUE = 0.000 <0.05 AND CONTINGENCY COEFFICIENT OF 0.420). ADVICE FOR HEALTH WORKERS, ESPECIALLY MIDWIVES ARE EXPECTED TO PROVIDE COUNSELING SERVICES, INFORMATION, EDUCATION AND COMMUNICATION (IEC) ABOUT MENOPAUSE SO THAT MOTHERS PRALANSIA BETTER PREPARED TO FACE THE MENOPAUSE.